NEW BODY TECHNOLOGIES: CHALLENGES FOR THE PHYSICAL EDUCATION (Fiep Bulletin - online, 2015)
This article aims at discussing the relations of the body in the contemporary culture, where it is mediatized, trespassed and invaded by the context of the new technologies with the implications and determinations that this context has been reflecting in the universe of Physical Education. This thematic in development by the doctorate student is a result of a research about the use of anabolic steroids by undergraduate students of Physical Education. New identities start to take shape when the body assumes an ever movable and mutant anatomy via the interpenetration of technology, which adds power to and maximizes the bodily performance. In the scenarios of sports and fitness, the doping, the anabolic steroids, and the supplements corroborate the enhancing of the body, elevating it to its highest potency. One of the questions posed by the research is the apparent displacement of the physical activity as a means of promoting health and good shape to a mere way of triggering the metabolic process of the psychopharmacological substances. In this way, the ethical implications of the professional actuation underlie the discussion, since  in a concealed consent  the use of these substances is becoming compulsory beyond the sports area, also affecting the scenario of physical activities.
Keywords: body; new technologies; social imaginary.